Optimal Magnetic Resonance Sequence for Assessment of Central Cartilage Tumor Scalloping - Kapil K. Shirodkar; Nathan Jenko; Christine Azzopardi; Jennifer Murphy; Anish Patel; Steven L. James; Arthur Mark Davies; Rajesh Botchu (Indian Journal of Radiology and Imaging, 2025)
Background Magnetic resonance imaging (MRI) is key in evaluating central cartilage tumors. The BACTIP (Birmingham Atypical Cartilaginous Tumour Imaging Protocol) protocol assesses central cartilage tumor risk based on the tumor size and degree of endosteal scalloping on MRI. It provides a management protocol for assessment, follow-up, or referral of central cartilage tumors.